Legal Analysis of Predatory Pricing Practices by Cross-Border Sellers on the Marketplace in the Perspective of Business Competition Law - Sri Fitrinah; Endang Sutrisno (CV. Syntax Corporation Indonesia, 2026)
The development of digital trade has encouraged the emergence of cross-border e-commerce that allows foreign sellers to market their products directly to consumers in Indonesia through marketplaces. This phenomenon raises the potential for predatory pricing practices, which are very low pricing strategies to get rid of competitors and dominate the market. This study aims to analyze the application of business competition law to predatory pricing practices by cross-border sellers in the marketplace and examine the juridical consequences it causes. The research method used was normative juridical with a legislative and conceptual approach, to various relevant legal sources. The results of the study show that the practice of predatory pricing is prohibited based on Article 20 of Law Number 5 of 1999. However, law enforcement against foreign business actors still faces obstacles in jurisdiction, proof, and supervision. This practice has the potential to harm MSMEs and creates unfair business competition. Therefore, it is necessary to strengthen ICC's regulations and authority to face the challenges of cross-border digital trade.